Strategi Pengunaan Gaya Bahasa pada Artikel Mojok Bertopik Virus Corona - Anharudin Nandiwardana; M. Suryadi (Program Studi Ilmu Perpustakaan, Fakultas Ilmu Budaya, Universitas Diponegoro, 2021)
Strategies of Language Styles Application on Corona Viruses Articles by Mojok. The focus of this study aims to reveal the alignment of the language style used in Mojok articles. More focused, this alignment was identified from articles that raised the issue of the Corona virus in Indonesia. The data studied were articles published by the editorial staff for one week when the government announced that a patient was identified with the Corona virus. From these data, found that articles on the mojok.co page generally use satirical style. This style then developed with satire, irony, and humorous nuance, according with their target audience, that mostly teenagers. Based on this style, basically Mojok still tries to criticize the mistakes that occur in society in a neutral way. The opinion that was built by Mojok during the emergence of the Corona virus in Indonesia was discuss misunderstandings of information received by the public. Editors have published many articles related to the dissemination of information and tips about the Corona virus so that the public is not consumed by hoax issues. Furthermore, the authors also found that the editorial team was also quite fierce in responding to mask hoarders who were looking for personal gain, and slightly criticized the government to be able to deal with the Corona virus in Indonesia.